How do you differentiate #f(x)=xe^x-x# using the product rule?
By signing up, you agree to our Terms of Service and Privacy Policy
To differentiate ( f(x) = xe^x - x ) using the product rule, we differentiate each term separately and then apply the product rule, which states that if ( f(x) = u(x)v(x) ), then ( f'(x) = u'(x)v(x) + u(x)v'(x) ).
Here's how we do it:
- Let ( u(x) = x ) and ( v(x) = e^x ).
- Find ( u'(x) ) and ( v'(x) ). ( u'(x) = 1 ) (derivative of ( x )) ( v'(x) = e^x ) (derivative of ( e^x ))
- Apply the product rule: ( f'(x) = u'(x)v(x) + u(x)v'(x) ) ( = (1)(e^x) + (x)(e^x) ) ( = e^x + xe^x )
So, ( f'(x) = e^x + xe^x ).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you find the derivative of #f(x)=ax+b#?
- How do you differentiate #f(x)=sqrt(tane^(4x)# using the chain rule.?
- How do you differentiate #g(y) =(2x-5 )(x^3 + 4) # using the product rule?
- How do you differentiate #f(x)=cos(sqrt((cosx^2))) # using the chain rule?
- How do you find the derivative of #g(x)=x^2+4x^3#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7